Development of microfluidics device for nanoparticles fabrication - Law, Geraldine Xue Ning (2015)
This final year project was set out to collect the findings of certain parameters that would affect the size of magnetite nanoparticles being produced. The parameters being investigated to affect the size of nanoparticles were the flow-rate of reactants injected into the microfluidic channels as well as the width of channels used. The procedures in fabrication of magnetite nanoparticles (Fe3O4) with citric acid as surface coating will be discussed in detail. The method of fabrication used in this project was the microfluidic channel device, with the co-precipitation mechanism of Fe2+ and Fe3+ ions. An improvement to the method of synthesis has been made, which is to use a one-step synthesis for the injection of citric acid into the microfluidic device.